2022
DOI: 10.1097/prs.0000000000008792
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Ultrasonography and Significance of Surgical Anatomy in the Management of de Quervain Disease: A Systematic Review and Meta-Analysis

Abstract: De Quervain stenosing tenosynovitis is characterized by swelling and thickening of the extensor retinaculum covering the first dorsal compartment, through which the abductor pollicis longus and extensor pollicis brevis tendons pass. [1][2][3] There exist notable variations in first dorsal compartment anatomy as described according to the Hiranuma classification. 4,5 Presenting patients report pain, swelling, and discomfort over the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Kulthanan and Chareonwat [ 33 ] investigated septal prevalence in patients with de Quervain compared to cadavers of assumably physiological states. The authors reported that septa were more commonly found in patients with de Quervain than in cadavers, which was in good agreement with systemic reviews of Lee et al [ 1 ], Bonczar et al [ 34 ] and Abi-Rafeh et al [ 31 ]. Therefore, the presence of an intra-compartmental septum within the 1st EC might also be associated with de Quervain tenosynovitis etiology or pathophysiology.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Kulthanan and Chareonwat [ 33 ] investigated septal prevalence in patients with de Quervain compared to cadavers of assumably physiological states. The authors reported that septa were more commonly found in patients with de Quervain than in cadavers, which was in good agreement with systemic reviews of Lee et al [ 1 ], Bonczar et al [ 34 ] and Abi-Rafeh et al [ 31 ]. Therefore, the presence of an intra-compartmental septum within the 1st EC might also be associated with de Quervain tenosynovitis etiology or pathophysiology.…”
Section: Discussionsupporting
confidence: 83%
“…The presence of intra-compartmental septa was attributed to the failure of conservative treatment (corticosteroid injection) for de Quervain tenosynovitis [ 5 , 11 ]. Several studies indicated that ultrasound-guided corticosteroid injection resulted in a superior accuracy over blind injections when sub-compartments were present within the 1st EC [ 4 , 8 , 30 , 31 ]. Therefore, we recommend ultrasound-guided corticosteroid injection over blind injection for conservative de Quervain tenosynovitis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the dorsal tubercle of the radius was emphasized in a Delphi study of anatomical structures useful to rheumatologists [ 17 ]. Pantukosit’s fascinating report [ 8 ] observed that all but one of 30 FIS cases occurred on the dominant side, and most of the patients were rice farmers who performed repetitive, forceful wrist movements. All the patients reported pain, while 22 experienced swelling and 12 had a tendon rub.…”
Section: Discussionmentioning
confidence: 99%
“…The EPB originates distal to the APL and joins it, following the same trajectory and relationships. These muscles extend obliquely in a lateral and caudal direction and reach the hand under the extensor retinaculum in the first dorsal compartment in a single synovial sheath, which is wholly or partially septated in approximately 40% of cadaveric specimens [ 8 ]. These tendons are inserted on the thumb, with the APL on the lateral side of the first metacarpal base and the EPB on the dorsal side of the proximal phalanx.…”
Section: Introductionmentioning
confidence: 99%
“…In a review and meta‐analysis by Abi‐Rafeh et al, incomplete septum and complete septum separation were not observed. Using a random effects model in the surgical population with clinical DQT (6 studies, 212 wrists), the general prevalence of intercompartmental septum was calculated to be 67% by Abi‐Rafeh et al 19 The septum prevalence in the general cadaver population was determined to be 35% (5 studies, 150 wrists) 19 …”
Section: Discussionmentioning
confidence: 99%